Arthrinium trachycarpum sp. nov. from Trachycarpus fortunei in China - Yan, He; Jiang, Ning; Liang, Ling-Yu; Yang, Qin; Tian, Cheng-Ming (Phytotaxa, 2019)
Arthrinium species are globally distributed on various substrates, especially on plant tissues as endophytes, saprobes, as well as pathogens. In present study, Arthrinium strains were obtained from diseased branches of Trachycarpus fortunei, and were compared with known species based on morphological characteristics and DNA sequence data. Thus, Arthrinium trachycarpum sp. nov. is introduced herein, which has shorter and narrower conidia than its most similar species, Arthrinium sinense.